Prediction of post-partum depression and anxiety based on clinical interviews and symptom self-reports of depression and anxiety during pregnancy. (1st June 2022) - Wilkie, E.; Gillet, V.; Talati, A.; Posner, J.; Takser, L.
Abstract : Introduction: The tools used to evaluate mental health during pregnancy matter. Their efficacy in identifying symptom severity enables better predictions of postpartum mental health. The Mother & Youth: Research on Neurodevelopment & behaviour (MYRNA) cohort is an NIH funded longitudinal cohort from Sherbrooke, Canada studying the effects of pregnant women's mental health. Objectives: We examine which mental health tools will better gauge depression and anxiety during pregnancy based on predicting postpartum outcomes. Our hypothesis is that an approach combining a clinical interview with self-report questionnaires may predict mental health in postpartum women. Methods: Participants' mental health is evaluated by the SCID-5-RV, a lifetime interview administered at 30 weeks and monthly questionnaires including PHQ-9 and GAD-7. Participants are in the depression/anxiety group if they either pass all the criteria in the SCID during pregnancy or have an average PHQ-9 or GAD-7 score greater than 7. The Edinburgh Postnatal Depression Scale (EPDS) and the Perceived Stress Scale (PSS) are the outcome variables. Results: PHQ-9 was correlated with EPDS, r (220)= .38, p < .01, and GAD-7 was correlated with PSS, r (213)= .56, p< .01. SCID results only had a significant effect on PSS, F (3, 220)= 3.77, p = .01 and not with EPDS, F (3, 219)= 1.08, p = .36. When the self-report measures and interview were combined significant effects were seen for both the EPDS, F (1, 222)= 18.71, p < .01 and the PSS, F (1, 223)= 34.94, p <.01. Conclusions: Preliminary results show significant associations between measures administered during pregnancy and postpartum measures. Prediction models based on classification will be analyzed once more data is collected. Disclosure: No significant relationships.